An investigation on a TMNET ISDN traffic in Shah Alam / Yatimulea Ramli - Ramli, Yatimulea (2003)
This paper is about an investigation on TMNET integrated services digital network (ISDN) traffic in Shah Alam. Traffic analysis is very important to network operations. The results obtained from traffic analysis can be used to improve the grade of service (GOS). Analysis is for a period of 8months, starting from August 2002 until March 2003.